The Role of Attention, Memory, and Metacognition in Student Learning Outcomes - Najmi Hayati (CV Najmi Edu Creative, 2026)
This study aimed to examine the role of attention, memory, and metacognition in predicting student learning outcomes in the Developmental Psychology course. Conducted in September 2025 in the Department of Islamic Religious Education, Faculty of Islamic Studies, Riau Islamic University, the research involved 101 third-semester students. Using a quantitative correlational design, data were collected through validated instruments: an Attention Assessment Scale, a Working Memory Questionnaire, and the Metacognitive Awareness Inventory (MAI). Student learning outcomes were measured using final course grades. Descriptive statistics, Pearson correlations, and multiple regression analyses were used to assess the relationships among variables. The results showed that attention, memory, and metacognition were each positively and significantly correlated with student learning outcomes. Regression analysis further indicated that metacognition was the strongest predictor, followed by memory and attention, collectively explaining a substantial proportion of variance in academic performance. These findings highlight the importance of strengthening cognitive and metacognitive skills to enhance learning outcomes in higher education settings